Experiential Learnings & Challenges: Community Extension Program of BSBA Human Resources Management - Dela Rosa, Robert Neil; Funelas, Jean Chesca; Malik, Jawhara; Ramirez, Fretzmar; Rulloda, Vanessa Earlynjohn; Santos, Jiro Daniel; Gapasin, Willy (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study examined the experiential learning of BSBA Human Resource Management students through community extension programs and its relationship with sustainability outcomes in Barangay 635 and Barangay 420. Anchored on David Kolb’s Experiential Learning Theory, the study emphasized learning through experience and reflection in real-life community settings. A cross-sectional analytical survey design was used, with purposive sampling involving individuals directly engaged in the Community Extension Program, including BSBA-HRM students and participating community residents. The study employed a researcher-developed survey instrument adapted from existing tools on experiential learning, skills development, and community engagement, and validated through adviser, faculty, expert review, and pilot testing. Findings showed that experiential learning was highly positive in terms of knowledge and skills development, with an overall weighted mean of 4.36, and values formation and social responsibility, with an overall weighted mean of 4.21. The application of Human Resource Management concepts was assessed as positive, with an overall weighted mean of 4.14. The results further revealed that the program supported sustainability outcomes by promoting capacity building, leadership development, livelihood initiatives, student competencies, social awareness, and community empowerment. A moderate positive relationship was found between experiential learning and sustainability outcomes, with a Pearson correlation coefficient of r = 0.65, leading to the rejection of the null hypothesis. The study aligns with SDG 4, Quality Education; SDG 8, Decent Work and Economic Growth; and SDG 17, Partnerships for the Goals. Its sustainability impact is reflected in educational, socio-economic, and community sustainability by strengthening student learning while supporting long-term community development.
Keywords: BSBA-HRM Students; Community Empowerment; Community Extension Programs; Educational Sustainability; Experiential Learning; Human Resource Management; Social Responsibility; Socio-Economic Sustainability; Sustainability Outcomes